Colossal piezomagnetic response in magnetically pressed Zr+4 substituted cobalt ferrites - Monaji Vinitha Reddy (Nature Portfolio, 2017)
Abstract A remarkable 111% increase in magnetostriction (λ) and 435% increase in strain sensitivity (dλ/dH) (compared to normally compacted (NC) unsubstituted CoFe2O4 (CFO)) of Zr+4 doped CFO sample, Co1.2Zr0.2Fe1.6O4, prepared by magnetic field assisted compaction, have been reported in this study. Magnetic field assisted compaction (MC) has been employed to process Zr-doped cobalt ferrites, Co1+xZrxFe2−2xO4 (0 ≤ × ≤ 0.4), to further improve the magnetoelastic properties. Saturation magnetization (M S ) and coercivity (H C ) increase from ~426 kA/m and ~4.4 kA/m respectively, for x = 0, to ~552 kA/m and ~7.11 kA/m respectively for x = 0.2. Dramatic increase in λ was observed for MC samples (~ −360 ppm and ~−380 ppm for x = 0 and x = 0.2 respectively) compared to the NC samples (~−181 ppm and ~−185 ppm for x = 0 and x = 0.2 respectively). A remarkable quadruple increase in dλ/dH was observed in Zr-doped (x = 0.2) cobalt-ferrite (~4.3 × 10−9 A−1m) compared to that of unsubstituted cobalt-ferrite (~1.24 × 10−9 A−1m), while a fivefold increase in dλ/dH was observed for magnetically compacted (MC) Zr doped cobalt ferrite (x = 0.2) (~4.3 × 10−9 A−1m) compared to normal compacted (NC) unsubstituted cobalt ferrite (~0.8 × 10−9 A−1m).